Time-dependent creep fatigue damage evolution in C/SiC composite: Theory and analytical prediction. Issue 14 (15th July 2022) - Li, Longbiao; Reynaud, Pascal; Fantozzi, Gilbert
Abstract: In this paper, the time-dependent damage evolution in carbon fiber-reinforced silicon carbide ceramic-matrix composites (C/SiC CMCs) under creep fatigue loading at elevated temperature was analyzed using a micromechanical approach. Synergistic effects of creep fatigue peak stress level and damage in the matrix and the interface on time-dependent damage evolution in C/SiC composites were analyzed. Next, relationships of time-dependent creep fatigue damage mechanisms, damage parameters, environmental temperature and duration were determined. Then, the effects of composite constituent properties, creep fatigue damage state, environmental temperature, and duration on time-dependent damage evolution in C/SiC composites were analyzed. Furthermore, time-dependent composite strain response and interface debonding and oxidation state in C/SiC composite under different creep fatigue peak stress levels were predicted. Under creep fatigue loading, the composite internal damage evolution contributed to the increased time/temperature-dependent composite peak strain. Hysteresis-based damage parameters were developed and utilized to monitor C/SiC composite internal damage evolution. Under creep fatigue loading, the hysteresis area and width increased with oxidation duration to a peak value and remained constant, and the hysteresis modulus decreased with oxidation duration.